Effect of Web-based diabetes training program on diabetes-related knowledge, attitudes, and skills of health professionals: A randomized controlled trial - (:unkn) unknown (WILEY, 2019)
Aim To determine the effect of a Web-Based Diabetes Training Program (WB-DTP) on the diabetes-related knowledge, attitudes, and skills of health professionals. Methods This was an experimental pretest-post-test with a 1 month follow-up study design that included a control group. The results of the power analysis suggested that 50 individuals with diabetes should be in both the intervention and the control groups. The WB-DTP was developed in accordance with the Effective Teaching Instruction Model.. Measures included the information form, Achievement Test (AT), Diabetes Attitudes Scale (DAS), and skill observation forms. The Wilcoxon's Signed Rank test, Mann-Whitney U-test, and Friedman test were used to analyze group differences on these measures. Results There was a significant difference between the AT post-test and the follow-up test scores of the intervention and control groups. No significant difference was present for the DAS post-test and follow-up scores between the intervention and control groups. A significant difference emerged on the Insulin Injection Skill Observation Form score between the intervention and control groups. In addition, there was a significant difference in the measurement level of blood glucose by the Glucometer Skill Observation Form between the intervention and control groups. Conclusions As a result, it was determined that the WB-DTP is effective in increasing the diabetes-related knowledge and skills of healthcare professionals. However, the program was not adequate at increasing the diabetes-related attitudes of health professionals.
Keywords: diabetes education; health professionals; in-service training; type 2 diabetes; Web-based education; EDUCATION-PROGRAM; SELF-MANAGEMENT